Magnetic-Optic Effect-Based Topological State: Realization and Application - Wang, Xinyue; Zhao, Wen; Zhang, Hongyu; Elshahat, Sayed; Lu, Cuicui (Frontiers in Materials, 2022)
The topological state in photonics was first realized based on the magnetic-optic (MO) effect and developed rapidly in recent years. This review summarizes various topological states. First, the conventional topological chiral edge states, which are accomplished in periodic and aperiodic systems based on the MO effect, are introduced. Some typical novel topological states, including valley-dependent edge states, helical edge states, anti-chiral edge states, multimode edge states with large Chern numbers in two-dimensional and Weyl points in three-dimensional have been introduced. The manifest point of these topological states is the wide range of applications in wave propagation and manipulation, to name a few one-way waveguides, isolator, slow light, and nonreciprocal Goos-Ha ̈nchen shift. This review can bring comprehensive physical insights into the topological states based on the MO effect and provides reference mechanisms for light one-way transmission and light control.